2021
DOI: 10.2478/ncr-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

From Waste to Resource – Utilising Residue from Ready-Made Concrete as New Aggregate

Abstract: A new admixture is available, to reduce the sludge produced from the cleansing of production and transportation equipment in the fresh concrete industry. The result is agglomerations of hardening concrete, that might be utilised for aggregate. Utilisation depends on adequate properties. This paper reports from investigations on the physical and mechanical properties of the aggregate and discussions on the performance relative to natural and recycled aggregates and towards requirements for utilisation. The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Other studies have also reported the density for recycled aggregates obtained from ready mixed concrete waste within the range 1.65-2.72% [11,16,20,26]. It can also be mentioned that Norwegian rocks typically have a density within the range of 2.65-3.10 g/mL [16]. The values obtained for density clearly show that RCZ have similar density characteristics compared to other recycled and natural aggregates.…”
Section: Physical Propertiesmentioning
confidence: 66%
See 4 more Smart Citations
“…Other studies have also reported the density for recycled aggregates obtained from ready mixed concrete waste within the range 1.65-2.72% [11,16,20,26]. It can also be mentioned that Norwegian rocks typically have a density within the range of 2.65-3.10 g/mL [16]. The values obtained for density clearly show that RCZ have similar density characteristics compared to other recycled and natural aggregates.…”
Section: Physical Propertiesmentioning
confidence: 66%
“…Given the variation of WA in RCSA, it is important to consider factors such as substitution level and water-cement ratio if used in concrete. [16,23]. Overall, the results demonstrated that RCZ have better quality performance.…”
Section: Physical Propertiesmentioning
confidence: 76%
See 3 more Smart Citations